A problem-/case-based learning approach as an useful tool for studying glycogen metabolism and its regulation - García-Ponce, Ángel Luis; Martínez-Póveda, Beatriz Amparo; Blanco-López, Ángel; Rodríguez-Quesada, Ana María; Suárez-Marín, María Fernanda; Alonso-Carrión, Francisco José; Medina-Torres, Miguel Ángel (My University, 2020)
Metabolism and its regulation is one of the most complex and difficult topics for students learning biochemistry. A problem-/case-based learning (PBL) approach can be useful to help biochemistry students to fulfill the goal of acquiring an integrated view of metabolism and its regulation. The present article describes our experience enrolling volunteer students to learn glycogen metabolism making use of a design-based research methodology to develop teaching learning sequences focused on a PBL approach. Enrolled undergraduate students had better final scores than those students that did not participates. Furthermore, enrolled students were satisfied with the experience, finding it interesting, formative, and challenging.
Versión preprint del manuscrito de los autores, publicado finalmente en: Biochemistry and Molecular Biology Education, con DOI: 10.1002/bmb.21449
Keywords: Aprendizaje por experiencia; Metabolismo - Alteraciones; Metabolismo - Regulación; Glucógeno; Problem-based learning; Metabolismo y enfermedad; Glycogen